Transformation of Information Technology to Improve Human Resources of Farmers in the Indonesian Context: The Role of Farmer Cards - Harun, Dani Ramdani; Priyanto, Sony Heru; Suharti, Lieli (Technium Social Sciences Journal, 2021)
Different approaches in the introduction and socialization of farmer cards resulted in the adoption rate of farmers not following the planned target even though one of the objectives of the farmer card program was to improve farmer human resources. This study aims to analyze the perceived impact of the farmer’s card on the level of adoption and improvement of farmer’s human resources. Respondents selected based on cluster sampling came from the 6 districts that used the most farmer cards in Central Java. The data obtained through the survey were analyzed using Structural Equation Modeling. The five variables measured consisted of transformational leadership, the role of the government, facilitating conditions, perceived farmer cards, perceived farmer card adoption, and farmer human resources. The results showed that transformational leadership, the role of government, and facilitating conditions had a significant effect on perceived farmer cards. The perceived farmer card has a significant effect on the adoption of the farmer card. Adoption of farmer’s card has a significant effect on farmer’s human resources. The application of the farmer card results in a farmer database increased accuracy and government services to farmers. Future research needs to be directed at conducting development research related to increasing the capacity of farmer card information technology to make farmers more prosperous.